2019
DOI: 10.3389/fgene.2019.01089
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeography Analysis Reveals Population Dynamics and Genetic Divergence of a Widespread Tree Pterocarya stenoptera in China

Abstract: The geological events, past climatic fluctuations, and river systems played key roles in the spatial distribution, population dynamics, and genetic differentiation of species. In this work, we selected Pterocarya stenoptera, a widespread tree species in China, to test the roles of these factors. Four noncoding spacers, eight microsatellite (simple sequence repeat) markers, and species distribution modeling were used to examine the phylogeographical pattern of P. stenoptera. Based on chloroplast DNA data, popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
(78 reference statements)
2
6
0
Order By: Relevance
“…However, phylogeographic inference of P. stenoptera revealed three independent groups among the Chinese populations. In addition, it was suggested that past climate change and gene flow might have together determined the genetic structure of P. stenoptera (Qian et al, 2019). Here, our analyses revealed three independent genetic structures that are widely observed in other species (Gugger et al, 2011;Yu & Nason, 2013;Fu et al, 2014).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…However, phylogeographic inference of P. stenoptera revealed three independent groups among the Chinese populations. In addition, it was suggested that past climate change and gene flow might have together determined the genetic structure of P. stenoptera (Qian et al, 2019). Here, our analyses revealed three independent genetic structures that are widely observed in other species (Gugger et al, 2011;Yu & Nason, 2013;Fu et al, 2014).…”
Section: Discussionsupporting
confidence: 61%
“…Identification of population genetic structure at the genome-wide level can help to understand how these factors affected the formation of genetic structure. Recently, two studies have reported the population genetic structure of P. stenoptera (Li et al, 2018;Qian et al, 2019). The study of landscape genomics of P. stenoptera showed that populations in China were weakly subdivided into two groups, and environmental variables related to ecological niche play important roles in shaping population genetic structure (Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent common garden experiments, Arabidopsis halleri in metal-contaminated areas expressed adaptive differentiation in gene expression in response to high zinc stress, which indicates the differentiation of adaptive strategies among populations [ 10 ]. Under the same cultivation conditions, Ricotia lunaria showed significant differentiation of gene expression among different natural populations [ 11 ]. These studies indicate constitutive expression differences among different populations, even among those that are found in the same conditions or face to the same stresses.…”
Section: Introductionmentioning
confidence: 99%
“…Climatic oscillations and changes in geography associated with the Quaternary are generally considered to have been the main driver governing the region’s present plant distributions ( Hewitt 2004 ). During the last few decades, many studies on the genetic diversity and structure of plant species have sought to check this suggestion around East China Sea (ECS) ( Qiu et al 2009 ; Xu et al 2015 ; Tang et al 2017 ; Qian et al 2019 ). Such studies mainly have focused on Chinese or Japanese plants, or both.…”
Section: Introductionmentioning
confidence: 99%